APPLICATION OF GAMIFICATION IN HIGHER EDUCATION: TRAINING OF EARLY CHILDHOOD AND PRIMARY EDUCATION TEACHERS IN UKRAINE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Over the past five years, the issue of gamification of education in Ukraine has been actively discussed in academic community, expanding through the practice of innovative teachers, and the availability of online courses using various platforms and applications. But still, in some cases, the issue of gamification is reduced to the question of preparation for interaction during a traditional game. That is why we have addressed several issues in this scientific review. First, what is the difference between gamification of education and the use of games in the educational process. Secondly, we decided to analyse the gaming interests and preferences of young people who plan to work in educational institutions. This allowed us to outline not only the range of interests, but also to highlight the levels of student readiness to use gamification through the existing offer and develop their own game complexes for work in preschool or elementary schools. Thirdly, we analysed the market offer for primary and preschool education in terms of online exercises and applications that are comprehensive. This helped us to identify (from our point of view) a list of quality platforms and applications that are effective for development. They can be used in training as training examples for future teachers when studying teaching methods of various subjects, or used for school preparation, etc. In addition, we have partially repeated the reasons for confusion in terms and risks associated with the implementation of international experience in the practice of Ukrainian education due to the economic, social and military-political situation. We believe that such a comprehensive view of gamification in higher education in Ukraine will allow us to expand the scope of understanding and implementation of appropriate training for use by teachers and comprehensive multi-component social development of educational game content for preschool and primary education.